Symbology, Identity, and Show: Critical Analysis of Costume and Make-Up used in Modern-Day Nigerian Theatre Production - Oliogu, Tunde Obado (NIU Journal of Humanities, 2025)
The paper examines the role that costume in modern theatre in Nigeria plays as a signifier of identity, heritage, mood and narrative within a play. By use of qualitative, semiotic and case-study perspectives, it parallels the three principal processes, Saro the Musical, Kurunmi, and university theatre festivals, to interpolate how designers and directors deploy visual symbology in performance. The most important findings suggest that costume and make-up are not merely used to distinguish two or more characters, and so much more, they work to negotiate issues of class, ethnicity, gender, and urban/rural identity, and to situate indigenous aesthetics within contemporary design sensibilities. The paper also suggests a cost and materials issues faced by designers and that more documentation and training of designers need to be offered to develop creativity. These emphases on the visual aspects of theatre help to establish the paper within the Nigerian literature on performance, as well as to provide the recommendations on how to approach the need to fill the gap between design creativity and cultural integrity in the process. Keywords : Nigerian theatre, costume design, make‑up, visual semiotics, cultural identity, performance aesthetics.